2010
DOI: 10.1016/j.optlaseng.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser treatment of ZE41 magnesium alloy for corrosion resistance and microhardness improvement

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. a b s t r a c tA laser surface melting treatment (LSMT) was performed on a ZE41 Mg-alloy using an excimer KrF laser. The laser-melted layer depth depends on the laser scan speed. The morphology and the microstructure of the laser-melted surface were characterized, thanks to the scanning electron microscopy (SEM). The melted Mg-alloy presented a homogenous dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…Therefore, the laser-treated alloy became nobler than the untreated one. A similar result to this work was discussed by the authors Khalfaoui et al [19]. These same authors have also shown, when the laser-treated and untreated samples were exposed in a corrosive solution for 2 h, several corrosion pits were observed in the untreated surface while the laser-treated layer was unaltered.…”
Section: Corrosion Resistance Tafel Plots For Lsr-treated and Untreasupporting
confidence: 91%
“…Therefore, the laser-treated alloy became nobler than the untreated one. A similar result to this work was discussed by the authors Khalfaoui et al [19]. These same authors have also shown, when the laser-treated and untreated samples were exposed in a corrosive solution for 2 h, several corrosion pits were observed in the untreated surface while the laser-treated layer was unaltered.…”
Section: Corrosion Resistance Tafel Plots For Lsr-treated and Untreasupporting
confidence: 91%
“…The changes in both the structure and the morphology of phases triggered this way may lead to creating a material with a new spectrum of properties [1][2][3][4][5][6][7][8][9][10][11]. Modification of magnesium alloys surface layer is an interesting research issue of a high application potential [12][13][14][15][16][17][18][19]. These materials, rated as the most innovative and prospective metallic materials, are distinguished by low density and high specific strength.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many surface modification methods, laser surface treatment [6][7][8][9][10][11][12], including laser cladding has been used successfully to deposit different coating materials on Mg and its alloys in order to improve their corrosion and wear resistance. With regard to laser cladding of Zr on Mg, the early work of Subramanian et al [6] on the laser cladding of Mg-Zr alloys on Mg substrates showed that an excellent metallurgical bond was obtained.…”
Section: Introductionmentioning
confidence: 99%